2021
DOI: 10.21043/politea.v4i2.11735
|View full text |Cite
|
Sign up to set email alerts
|

Wacana Poros Partai Islam untuk PILPRES 2024: Politik Identitas atau Penggalangan Suara Oposisi?

Abstract: <p><em>Amidst increasing polarization of society after the 2014 and 2019 presidential elections, identity politics has been reintroduced by Islamic political parties. PKS and PPP are trying to initiate the Islamic pollitical axis for 2024 elections. The discourse about Islamic political axis springs due to the fact that incumbents cannot re-nominate as president for next election. Secondly, public trust level toward the executive has decreased due to various unpopular policies that brought about in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…This means that what is called an Islamic party includes both those that are based on Islam and those that are not based on Islam but are based on Islamic masses. Apart from according to experts, according to the public, referring to the results of the Indo Barometer national survey in December 2007, it was stated that in the Indonesian political constellation, the most prominent political party polarization is between the Islamic party and the Nationalist party (Hamdanny & Mukhtar, 2021).…”
Section: Islamic Political Partymentioning
confidence: 99%
See 1 more Smart Citation
“…This means that what is called an Islamic party includes both those that are based on Islam and those that are not based on Islam but are based on Islamic masses. Apart from according to experts, according to the public, referring to the results of the Indo Barometer national survey in December 2007, it was stated that in the Indonesian political constellation, the most prominent political party polarization is between the Islamic party and the Nationalist party (Hamdanny & Mukhtar, 2021).…”
Section: Islamic Political Partymentioning
confidence: 99%
“…According to some groups, the existence of parties in the name of religion creates polemics in the country, this is because the existence of parties with certain views causes political parties to fall into sectarian politics (Hamdanny & Mukhtar, 2021). The 2014 elections which were participated by 12 national political parties and added by 3 local political parties (specifically for Aceh) showed that the results of the 2014 Legislative Election which had been announced by the KPU placed ten parties that passed the parliamentary threshold, namely the NasDem Party, PKB, PKS, PDIP, Golkar Party, Gerindra Party, Democratic Party, PAN, PPP, and Hanura Party.…”
Section: Introductionmentioning
confidence: 99%
“…Syahriel mengembangkan pendekatan komunikasi politik yang mengutamakan interaksi komunikator politik dengan publik yang lebih luas. Dalam upaya meraih kekuasaan, dilakukan upaya untuk memperkokoh kohesivitas sosial, yang secara tidak langsung juga memperkuat kepercayaan masyarakat (Hamdanny, 2021). Komunikator politik yang efektif adalah orang yang sadar diri, dapat dipercaya, menarik, dan kuat (Gandasari, 2021).…”
Section: Kepedulian Sosialunclassified
“…Akibatnya adalah distrust oleh publik terhadap pemerintah termasuk ke Presiden cenderung stagnan bahkan menurun (Cornelia Evelin Cabui, 2022;Powell, 2021). Kondisi ini benar-benar memposisikan pemerintahan pada pilihan kelihatan sulit, di suatu sisi, berpikir terhadap pemulihan ekonomi pasca Pandemi Covid-19, tetapi di sisi lain beban utang negara terhadap negara lain juga mengalami peningkatan, resesi ekonomi dan keuangan yang di alami oleh negara kemungkinan menjadi alasan fundamental sehingga kebijakan demi kebijakan lahir dan diterapkan tanpa memperhatikan asas proporsionalitas sehingga kerap muncul kritik dan kontraproduktif dari sejumlah kalangan dan publik pada umumnya (Hamdanny & Mukhtar, 2021).…”
Section: Pendahuluanunclassified
“…Bongkar pasang pejabat negara dari level kementerian hinggal level pemerintah daerah, pun dinilai menjadi salah satu anomali dalam mengadirkan transformasi pemerintahan yang lebih berpihak teradap kepentingan publik. Anomali tersebut adalah bagian atas dampak kebijakan presidential threshold (Ansori, 2019;Hamdanny & Mukhtar, 2021;Listyaningsih et al, 2020;Muhammad Saad, 2021;Mukhtarrija et al, 2017). Sejumlah referensi dengan cukup hati-hati menyuguhkan penjelasan terkait threshold, karena memang memiliki varian beragam antara lain adalah electoral threshold, parlimentary threshold dan presidential threshold.…”
Section: Presidential Threshold: Antara Disrupsi Dan Keadilan Demokrasiunclassified